Overexpression of lncRNA TUG1 Alleviates NLRP3 Inflammasome-Mediated Cardiomyocyte Pyroptosis Through Targeting the miR-186-5p/XIAP Axis in Coronary Microembolization-Induced Myocardial Damage - Zhou, You; Li, Tao; Chen, Zhiqing; Huang, Junwen; Qin, Zhenbai; Li, Lang (Frontiers in Immunology, 2021)
Coronary microembolization (CME) is a complicated problem that commonly arises in the context of coronary angioplasty. The lncRNA taurine-upregulated gene 1 (TUG1) which significantly contributes to cardiovascular diseases, however, its contribution to CME-induced myocardial damage remains elusive. Herein, we established the rat CME model and investigated the role of TUG1 in CME. The cell viability was evaluated via CCK-8 assay. Serum and cell culture supernatant samples were evaluated via ELISA. The dual luciferase reporter (DLR) assay, RIP, and RNA-pulldown were conducted to validate the associations between TUG1 and miR-186-5p, as well as miR-186-5p and XIAP. The expression of TUG1, miR-186-5p, and XIAP mRNA were determined by RT-qPCR, and proteins were evaluated via immunoblotting. As a result, the TUG1 and XIAP were significantly down-regulated, while the miR-186-5p level was found to be remarkably upregulated in CME myocardial tissues. Overexpression of TUG1 alleviated CME-induced myocardial injury and pyroptosis, whereas TUG1 knockdown showed the opposite effects. The DLR assay, RIP, and RNA-pulldown results revealed that TUG1 directly targeted on miR-186-5p and miR-186-5p directly targeted on XIAP. In vitro rescue experiments showed that TUG1 overexpression alleviates LPS-caused cardiomyocyte injury and pyroptosis via sponging miR-186-5p and regulating XIAP, and depression of miR-186-5p reduces LPS-induced cardiomyocyte injury and pyroptosis by targeting XIAP. Concludingly, the overexpression of TUG1 alleviates NLRP3 inflammasome-mediated cardiomyocyte pyroptosis through targeting the miR-186-5p/XIAP axis in CME-induced myocardial injury.